The Effect of Financial Planning, Budgeting and Estimation in the Business Plan - Antonius, Antonius; Argunanto, Argunanto; Wulan, Defina Andany; Zahra, Indri Eliza; Arifin, Deni; Anjelia, Viona; Suripto, Suripto; Holiawati, Holiawati (Institut Bisnis dan Informatika Kesatuan, 2024)
Hospital financial planning is basically a process of analysis, policy and projection that aims to help organizations achieve financial success. Budgeting is needed to allocate costs to certain activities that have been planned for a predetermined period of time. In addition, estimation is used as a systematic assessment tool for the success and/or failure of a policy or program in achieving the goals and objectives that have been set because estimation is an activity to track business performance whether it is in accordance with expectations or not. However, the lack of employee understanding of financial planning, budgeting and estimation has an impact on the efficiency and effectiveness of fund management. In addition, the lack of access to accurate financial data is a challenge in decision making. Therefore, training and socialization are very important for financial employees. With increasing literacy in Planning, Budgeting and Estimation, employees of PT. Medikarya Utama are expected to be able to carry out operational efficiency of the company.